A Need Analysis of English Learning for Economic and Business Students at dr. Soebandi University - Hamliyah, Hamliyah; Untari, Dewi; Lutfiah, Lutfiah; Yuliana, Siti; Agustini, Setyorini Dwi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Analysing English learning for Economics and Business students at dr. Soebandi University involves examining how English material and instruction is tailored to meet their specific academic and professional needs. In digital era of global economy, proficiency in English is crucial for accessing international markets, participating in global business networks, and understanding global economic trends. Thus, this study is to find out how English language learning is designed for students in economics and business disciplines and its impact on their academic and professional success. The qualitative method is applied to investigate the Needs Analysis. The data is collected through questionnaire and interviews to gather all information to improve the materials design of English for Economic and Business subject. There were 30 students of Economic and Business Faculty at dr. Soebandi University, and two lecturers. The finding of the study shows material relevance content, task-based learning and technology enhance materials that needed and should be improved in designing effective materials for Economics and Business students, which  preparing them for both academic and professional success.